Red Phosphorus Nanoparticle@3D Interconnected Carbon Nanosheet Framework Composite for Potassium‐Ion Battery Anodes. Issue 33 (19th July 2018) - Xiong, Peixun; Bai, Panxing; Tu, Shuibin; Cheng, Mingren; Zhang, Jinfeng; Sun, Jie; Xu, Yunhua
Abstract: Red phosphorus (P) has been recognized as a promising storage material for Li and Na. However, it has not been reported for K storage and the reaction mechanism remains unknown. Herein, a novel nanocomposite anode material is designed and synthesized by anchoring red P nanoparticles on a 3D carbon nanosheet framework for K‐ion batteries (KIBs). The red P@CN composite demonstrates a superior electrochemical performance with a high reversible capacity of 655 mA h g −1 at 100 mA g −1 and a good rate capability remaining 323.7 mA h g −1 at 2000 mA g −1, which outperform reported anode materials for KIBs. The transmission electron microscopy and theoretical calculation results suggest a one‐electron reaction mechanism ofP + K + + e − → KP, corresponding to a theoretical capacity of 843 mA h g −1, which is the highest value for anode materials investigated for KIBs. The study not only sheds light on the rational design of high performance red P anodes for KIBs but also offers a fundamental understanding of the potassium storage mechanism of red P. Abstract : A red phosphorous nanoparticle@carbon nanosheet composite is developed for potassium‐ion battery anodes and demonstrates a high reversible capacity of 655 mA h g −1 and outstanding rate capability. A one‐electron reaction mechanism of P + K + + e − → KP is proposed on the basis of experimental and theoretical thermodynamics studies, corresponding to a theoretical capacity of 843 mA h g −1 for red phosphorous.